2015
DOI: 10.1037/a0039661
|View full text |Cite
|
Sign up to set email alerts
|

Redesigning community mental health services for urban children: Supporting schooling to promote mental health.

Abstract: Objective This study examined a school- and home-based mental health service model, Links to Learning (L2L), focused on empirical predictors of learning as primary goals for services in high poverty urban communities. Method Teacher key opinion leaders (KOLs) were identified through sociometric surveys and trained, with mental health providers (MHPs) and parent advocates (PAs), on evidence-based practices to enhance children’s learning. KOLs and MHPs co-facilitated professional development sessions for class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 68 publications
1
44
0
1
Order By: Relevance
“…The therapy outcomes are consistent with those reported from the partner hospital's outpatient psychiatry service, which serves similarly complex populations of children and adolescents, while the targeted group intervention findings are consistent with outcomes of community‐based health promotion programs in general, where improvements have historically ranged from 1% to 15% . The student outcomes of the current study are also consistent with those observed in other recent comprehensive school‐based MH programs targeting demographically similar students . Even relatively modest improvements such as demonstrated in these studies, when extrapolated to large populations, have the potential for a significant public health and educational impact …”
Section: Discussionsupporting
confidence: 85%
“…The therapy outcomes are consistent with those reported from the partner hospital's outpatient psychiatry service, which serves similarly complex populations of children and adolescents, while the targeted group intervention findings are consistent with outcomes of community‐based health promotion programs in general, where improvements have historically ranged from 1% to 15% . The student outcomes of the current study are also consistent with those observed in other recent comprehensive school‐based MH programs targeting demographically similar students . Even relatively modest improvements such as demonstrated in these studies, when extrapolated to large populations, have the potential for a significant public health and educational impact …”
Section: Discussionsupporting
confidence: 85%
“…We examined the effectiveness of the service model in a three-year study in six schools with kindergarten-to-third grade children and results were promising. L2L, as compared to community-based mental health services as usual, produced significant positive effects on mental health service use, classroom observations of academic engagement, teacher report of academic competence and social skills, and parent report of social skills (Atkins et al, 2015). Though other goals, such as improved reading, were not realized, suggesting the need for further refinement of the service model, the study reinforced the value of coordination across schools and mental health agencies, and the feasibility of implementation of prevention-to-intervention strategies with goals common to both service sectors.…”
Section: Evolution Of An Ecological Public Health Model: Schools As Cmentioning
confidence: 99%
“…BRIDGE is based on two models: (a) MyTeachingPartner (MTP: Pianta, Mashburn, Downer, Hamre, & Justice, 2008; Allen, Pianta, Gregory, Mikami, & Lun, 2011), a teacher professional development program, and (b) Links to Learning (L2L: Atkins et al, 2008; 2015; Cappella et al, 2008), a mental health services model. Like MTP, BRIDGE is rooted in the CLASS, a standardized and validated observational tool for understanding and assessing effective classroom practices (Pianta, LaParo, & Hamre, 2008).…”
Section: Bridge Teacher Consultation and Coaching: Intervention Overviewmentioning
confidence: 99%
“…However, significant heterogeneity in implementation was observed. This is not unusual in intervention trials in which the intervention is delivered by school-based personnel rather than paid consultants, university personnel, or research staff (e.g., Aber et al, 1997; Atkins et al, 2015). Moreover, BRIDGE was designed to match classroom and student need, increasing the likelihood of variation in implementation.…”
Section: Bridge Intervention Effects and Implementation Questionsmentioning
confidence: 99%